Cognitive fatigability and neuronal correlates in chronic pain – A cross-sectional fMRI study - Anna Holmqvist; Love Engström Nordin; Nils Berginström; Monika Löfgren; Lars Nyberg; Britt-Marie Stålnacke; Marika C. Möller (PLoS ONE, 2025)
Objectives Fatigue is common in patients with chronic pain. However, there is a knowledge gap concerning performance fatigue, cognitive fatigability, and its neural correlates in this patient group. In this study, we therefore aimed to investigate the presence of cognitive fatigability and its neural correlates in patients with chronic pain using functional magnetic resonance imaging (fMRI). Methods In this study 24 women with chronic pain and 22 healthy controls, aged 18–45 years, underwent a 20-minute psychomotor vigilance task (PVT) assessing reaction time during blood-oxygen-level dependent (BOLD) fMRI. Reaction time and BOLD signal changes were analyzed using dual regression. Results The patients showed significant cognitive fatigability, i.e., prolonged reaction time, during the PVT, while the controls maintained a stable performance ( p = .018). No significant neural time on task effect was found on BOLD fMRI. There were however differences in the brain areas activated between the groups throughout task performance. Patients with chronic pain showed stronger activation primarily in prefrontal cortex, including motor areas, while healthy controls demonstrated stronger activation particularly in the left middle orbital gyrus and right insula. Conclusion The study indicates that the phenomenon of cognitive fatigability is present in patients with chronic pain. Also, the presence of chronic pain was associated with increased activation in brain regions related to motor and cognitive control, possibly reflecting compensatory mechanisms. Conversely, healthy controls showed higher activity in regions active in motivation, reward, and decision-making, suggesting more motivation-driven and efficient processing. Further studies are needed to validate the results.